NEAR-SOLIDUS MELTING OF THE SHALLOW UPPER MANTLE: PARTIAL MELTING EXPERIMENTS ON DEPLETED PERIDOTITE - Wasylenki L.E.; Baker M.B.; Kent A.J.R.; Stolper E.M. (My University, 2003)
We present the results of melting experiments on a moderately depleted peridotite composition (DMM1) at 10 kbar and 1250–1390°C. Specially designed experiments demonstrate that liquids extracted into aggregates of vitreous carbon spheres maintained chemical contact with the bulk charge down to melt fractions of ~0·02–0·04 and approached equilibrium closely. With increasing melt fraction, SiO2, FeO*, and MgO contents of the partial melts increase, Al2O3 and Na2O contents decrease, and CaO contents first increase up to clinopyroxene-out at a melt fraction of 0·09–0·10, then decrease with further melting. A linear fit to melt fraction vs temperature data for lherzolite-bearing experiments yields a solidus of 1272 ± 11°C. The melting reaction is 0·56 orthopyroxene + 0·72 clinopyroxene + 0·04 spinel = 0·34 olivine + 1 liquid. Above clinopyroxene-out, the reaction is 1·24 orthopyroxene = 0·24 olivine + 1 liquid. Near the solidus, DMM1 glass compositions have lower SiO2, TiO2, Na2O, and K2O contents, higher FeO*, MgO, and CaO contents, and higher CaO sol Al2O3 ratios compared with glasses from low-degree melting of fertile peridotite compositions. Recent computational models predict partial melting trends generally parallel to our experimental results. We present a parameterization of 10 kbar peridotite solidus temperatures suggesting that K2O and P2O5 have greater effects on solidus depression than Na2O, consistent with theoretical expectations. Our parameterization also suggests that abyssal peridotites have 10 kbar solidi of ~1278–1295°C.
Keywords: depleted; experimental petrology; mantle melting; near-solidus; peridotite